Breaking a dative bond with mechanical forces - Pengcheng Chen (Nature Communications, 2021)
Controlled breaking of a chemical bond by mechanical forces can provide key insight into reaction mechanisms. Here the authors, using atomic force microscopy and computations, measure the forces involved in breaking a single dative bond between a CO molecule and a ferrous phthalocyanine complex.